Legal Review of Medical Emergencies Arising Due to Failure of Abortion - Rizky Nurlailatul Wachidah (Borong Newinera Publisher, 2021)
The purpose of this article is to investigate the legal responses to botched abortions. the main characteristics of this style of study are normative juridical, with a combination of a philosophical framework and legislation Following the outcome of the abortion attempt, Article 53 of the Criminal Code was violated, along with those who assisted in the procedure and those who were victimized. Should an abortion result in the baby's death under article 346, 347, 348, and 349 of the Criminal Code Criminals may commit the crimes individually or in tandem. Hence, they are justly prosecuted, so that they can be designated as criminals or assistants. Article 50 was developed in response to failures by the abortion business; and it can't be penalized unless done in compliance with technical and organizational quality procedures. In general, you do not need a permit to use emergency measures. This does not extend to abortions carried out on the basis of medical emergencies except during counselling prior to and during the act of abortion in compliance with Article 75 of Law No. 36 of 2009.